EVALUASI PROFIL TPACK UNTUK GURU MATEMATIKA SEKOLAH MENENGAH PERTAMA DI BANTEN - Restiana, Nena (Universitas Negeri Semarang, 2018)
Information and Communication Technology (ICT) has an influence overall areas, as well as on learning. Learning is required to adjust the development of ICT to make learning more effective and dynamic. Constraints faced in the implementation of ICT. It is the underlying to do research related to the teacher's understanding of technology. This study will analyze the profile of technological understanding of juniorhigh school mathematics teachers using TPACK framework. Furthermore, age factor, length of teaching, and gender are analyzed its effect on TPACK using analysis of variance (ANOVA). The results of this study are six validated TPACK components, obtained five components namely TK, CK, PCK, TPTCK, TPCK. Based on the TPACK framework of junior high school mathematics teachers in Banten obtained the highest average score on the CK component. Age factor, duration of teaching and gender have no significant effect or only small effect on the five components of TPACK